Twenty years of in-situ monitoring in the south-eastern Mediterranean Levantine basin: Basic elements of the thermohaline structure and of the mesoscale circulation during 1995-2015 - Zodiatis, George; Brenner, Steve; Gertman, Isaac; Ozer, Tal; Simoncelli, Simona; Ioannou, Marinos; Savva, Sotiris (Frontiers in Marine Science, 2023)
Following the pioneering POEM cruises in the mid to late 1980’s, in-situ data collected over two decades since mid-1990s in the Southeastern Levantine Basin from 30 hydrographic campaigns and 35 bi-weekly and monthly Voluntary Observing Ships transects, have provided new insight and details on the dominant mesoscale coherent circulation features of this sub-basin. The most pronounced feature, the anticyclonic Cyprus Eddy, migrates over the broad region of the Eratosthenes seamount while exhibiting significant seasonal and inter-annual spatial-temporal variability. Another prominent structure, located further to the east, is the anticyclonic Shikmona Eddy generated by instabilities of the strong, northward jet flowing along the southeastern shelf and slope of the Levantine basin. Its evolution and co-existence with the Cyprus Eddy, lead to the periodic re-establishment of the Shikmona Gyre, which was first observed during the POEM cruises. The offshore, cross basin, eastward flowing mid-Mediterranean Jet (MMJ) defines the northern and southern flanks of these sub-basin scale anticyclonic eddies and transports the lower salinity modified Atlantic water (MAW) in the subsurface layer, from the Ionian Sea and through the warmest and most saline waters of the Mediterranean. Periodically, the MMJ bifurcates and/or is diverted northward, along the western coast of Cyprus due to westward and northward spatial fluctuations of the Cyprus Eddy’s western boundaries. The long term, in-situ monitoring of this sub-basin presented here, provides an overview of the extent of the main water masses and characterizes their variability throughout the period considered. Analysis of the data indicates an increase of the temperature and salinity of the Levantine Surface Water and of the subsurface MAW. The Eastern Mediterranean Transient Water is shown to occupy the deep cavities in the vicinity of the Eratosthenes seamount while its upper boundary was lifted to shallower depths during these two decades.